Mewujudkan Madrasah Ibtidaiyah Ramah Anak - rahmad, rahmad (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
Achievements in the development of national education must be strengthened by certainty, adequacy or contribution, affordability, quality, as well as equality and guarantees for children's educational rights without exception. This right is also given to all children such as disabled communities, victims of natural disasters, street children and even children who are dealing with legal issues and children who need other special protection. This article is a study material for the community to see education as a very important thing. Incorrect and opening opportunities for children to support school activities such as planning, implementing policies, then student-oriented learning, then there is a supervision system and there are mechanisms related to complaints against the fulfillment of children's rights and child protection. This paper is a study or study through a legal basis related to child-friendly school policies held at the level of basic education. Forms of violence in the school environment that can inhibit the predicate of a school can be said to be child-friendly school. Education units must eliminate violence and discrimination and unfair treatment. Child-friendly schools are a hope for further efforts to improve the quality of education in Indonesia. Another problem faced by the education sector is the practice of bullying and cyberbullying. In addition, the government program to improve the process and output of education through a program to strengthen character education that aims to make the etiquette or ethics of students getting better